MODIFIKASI METODE ISOLASI DNA CETYL TRIMETHYLAMMONIUM BROMIDE (CTAB) UNTUK SAMPEL EPITEL PIPI MANUSIA - Maharani Pertiwi Koentjoro; Hidayah Sri Wilujeng; Astrina Dilla; Endry Nugroho Prasetyo (Journal of Indonesian Medical Laboratory and Science, 2021)
Isolation of deoxyribonucleotide (DNA) is an important step in molecular analysis. In this process, DNA must be obtained in sufficient quantities and in good quality for any further analysis. The Cetyl Trimethylammonium Bromide (CTAB) method is commonly used in DNA isolation of plant or fungal. This method is an alternative in DNA isolation since it is easy and inexpensive. This study aims to modify the CTAB method for DNA isolation from human cheek epithelium for any molecular analysis. Epithelial cells were taken from the oral cavity of the researcher. The isolation protocol included cell lysis step with CTAB buffer and proteinase-K, purification step with the addition of chloroform:isoamylalcohol (24:1), precipitation step with isopropanol. The results of the ratio analysis of DNA spectrophotometer at wavelengths of 260 and 280 nm in the range of 1.73-1.85. The quality of DNA isolation was observed by agarose gel electrophoresis and a firm band was obtained after Ethidium Bromide staining. The DNA concentration in both methods ranged from 400-480 mg/mL. The time required for both methods ranges from 2.5-3 hours. The modified CTAB method DNA isolation protocol produces DNA that has good quality and quantity for molecular analysis processes, such as Polymerase Chain Reaction (PCR).